Bread freezing as a new alternative to consumption - Pascoalino, Liege (2022)
The growing consumer interest in health and food safety, as well as the increased consumption of fresh food, make frozen bread an increasingly popular alternative. This type of bread has several advantages, such as, large-scale manufacturing, economize manpower and equipment, and lowering production costs. Furthermore, one of the ways to extend shelf-life of ready-to-eat bread is to use deep freezing systems [1– 3]. In the present study, the effect of frozen storage time on the bread quality made from frozen dough, were studied, through the nutritional and chemical composition evaluation. Six equal multicereal breads were frozen, submitted to different storage times under deep freezing (190, 225, 251, 310, 344 and 694 days), and compared to the fresh multicereal bread. The nutritional profile was evaluated through the protein, ash, fat, and carbohydrate content, using official analysis methodologies (AOAC) and the energetic value was also estimated. The chemical composition regarding sugars and fatty were determined by chromatographic techniques, using a HPLC- RI and a GC-FID, respectively. In general, the results revealed that moister content is similar in all frozen breads, with values around 40%, while the fresh bread showed a content of 43.4%. The ash content presented values ranging between 1.51 ± 0.02 and 1.02 ± 0.02 g/100 g fresh weight (fw); and the mean value of the protein content in the samples was approximately 7 g/100 g fw. On the other hand, fiber showed values of 4% of total dietary fiber (TDF) fw for breads with longer frozen time, while the bread frozen for less time (190 days) and fresh bread showed values around 6% TDF fw. The fat content was also variable between fresh and frozen breads, however, the presence of polyunsaturated fatty acids (PUFA) in all samples was predominant, namely linoleic acid (C18:2n6c). Regarding the sugars profile, fructose, glucose, and maltose were detected in all bread samples, showing a total sugar value between 1.78 and 2.97 g/100g fw; and as expected, the most abundant sugar was maltose, a common sugar found in cereal. Regarding the carbohydrate evaluation, the obtained results ranged between 40.4 and 43 g/100g fw for frozen breads and 38.3 g/100 g fw for fresh bread; and the energetic value presented values greater than 220 kcal/100g in all samples. The results obtained show that freezing may be a promising alternative for bread conservation, contributing to the reduction of the high percentage of disposal that happens in all industrialized countries.